2015
DOI: 10.5455/medarh.2015.69.196-199
|View full text |Cite
|
Sign up to set email alerts
|

The First Report from Bosnia and Herzegovina on Micro-tese Results in Azoospermic Patients

Abstract: Introduction:To present results of MicroTese procedure in treatment of male infertility in patients with azoospermia at Bahçeci BIH IVF Center during two-year period of 2013-2014.Methods:In the stated time-period, 55 MicroTese surgeries were performed. In 52.7% of the cases, sperm cells were isolated after MicroTese surgery, and in 47.3% of the cases, there was a negative outcome of the procedure. Obtained sperm cells were subjected to cryopreservation. Furthermore, ICSI procedure was performed by use of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
0
7
0
1
Order By: Relevance
“…These resulted in 41 clinical pregnancies (44.6%) and 26 live births (28.3%). Various authors have reported clinical pregnancy and live birth rates ranging from 26 to 57% for NOA [28–32]. All our patients had single ICSI cycles.…”
Section: Discussionmentioning
confidence: 83%
“…These resulted in 41 clinical pregnancies (44.6%) and 26 live births (28.3%). Various authors have reported clinical pregnancy and live birth rates ranging from 26 to 57% for NOA [28–32]. All our patients had single ICSI cycles.…”
Section: Discussionmentioning
confidence: 83%
“…The standard for positive TESE procedure is 80-100% and for micro-TESE is about 50% whereas in recent studies the result is up to 60% (5, 6). Resent study from same group, prof.dr Ümit Göktolga et al had 52,7% positive sperm retrieval rate (SRR), and we have to consider that our examined group is smaller 21 patients, than 55 patients early examined (7). Relationship between etiological factors and determitants shows that most of patient had inguinal operations, orchidopexy or inginal canal repair (30%) and infections such parotitis and epididymoorchitis (20%) were in correlation with azoospermia in patients (8).…”
Section: Discussionmentioning
confidence: 93%
“…The standard for positive TESE procedure is 80-100% and for micro-TESE is about 50% whereas in recent studies the result is up to 60% ( 5 , 6 ). Resent study from same group, prof.dr Ümit Göktolga et al had 52,7% positive sperm retrieval rate (SRR), and we have to consider that our examined group is smaller 21 patients, than 55 patients early examined ( 7 ). Relationship between etiological factors and determitants shows that most of patient had inguinal operations, orchidopexy or inginal canal repair (30%) and infections such parotitis and epididymoorchitis (20%) were in correlation with azoospermia in patients ( 8 ).…”
Section: Discussionmentioning
confidence: 96%